Antiviral activity of casein and αs2 casein hydrolysates against the infectious haematopoietic necrosis virus, a rhabdovirus from salmonid fish - Rodríguez Saint-Jean, S; De las Heras, A; Carrillo, W; Recio, I; Ortiz-Delgado, J B; Ramos, M; Gomez-Ruiz, J A; Sarasquete, C; Pérez-Prieto, S I (Journal of fish diseases, 2013)
Salmonid fish viruses, such as infectious haematopoietic necrosis virus (IHNV), are responsible for serious losses in the rainbow trout and salmon‐farming industries, and they have been the subject of intense research in the field of aquaculture. Thus, the aim of this work is to study the antiviral effect of milk‐derived proteins as bovine caseins or casein‐derived peptides at different stages during the course of IHNV infection. The results indicate that the 3‐h fraction of casein and αS2‐casein hydrolysates reduced the yield of infectious IHNV in a dose‐dependent manner and impaired the production of IHNV‐specific antigens. Hydrolysates of total casein and αS2‐casein target the initial and later stages of viral infection, as demonstrated by the reduction in the infective titre observed throughout multiple stages and cycles. In vivo, more than 50% protection was observed in the casein‐treated fish, and the kidney sections exhibited none of the histopathological characteristics of IHNV infection. The active fractions from casein were identified, as well as one of the individual IHNV‐inhibiting peptides. Further studies will be required to determine which other peptides possess this activity. These findings provide a basis for future investigations on the efficacy of these compounds in treating other viral diseases in farmed fish and to elucidate the underlying molecular mechanisms of action. However, the present results provide convincing evidence in support of a role for several milk casein fractions as suitable candidates to prevent and treat some fish viral infections.